PULP OBTAINING METHOD FOR PACKAGE PRODUCTION - V. V. Kuzmich (Наука и техника)
The paper presents a new method for obtaining pulp which is used for production of cardboard, paper and package while using carbon dioxide and hydrazine hydrate and neutral-sulfite  shive cooking. Output increase of  the desired product can be explained by reduction in destruction of plant raw material carbohydrates during its cooking process. Quality improvement of the desired product (improvement in bleaching and output) is attributed to the fact that usage of carbon dioxide and hydrazine contributes to provision of polysaccharide chain resistance to destruction due to the presence of  end links having structure of metasaccharinic and aldonic acids.The author has developed a new method for pulp obtaining on the basis of the executed investigations  and literature data.  СО2 and hydrazine hydrate have been used for obtaining pulp. Method invention concerns pulp obtaining and it can be used for paper and cardboard package manufacturing in pulp and paper industry.The method is to be carried in the following way: pulp-containing plant raw material is loaded into an autoclave and then aqua solution of sodium monosulfite containing hydrazine hydrate that constitutes 4–5 % of absolute dry pulp-containing raw material mass with liquid module 1:6–1:8 is supplied into the autoclave. The autoclave is closed for operation under pressure and the solution is carbonated under pressure which constitutes 5–8 % of absolute dry plant raw material (shover). Temperature is subsequently raised up to 180 °С in the space of 2 hours and cooking is carried out in the course of 4 hours. Usage of  the proposed method for shover cooking makes it possible to reduce monosulfite cooking process and improve qualitative characteristics and output of the desired product.  In addition to above mentioned fact there is a possibility to improve bleaching and final product output.